Tissue integrity, costs and time associated with different agents for histological bone preparation. Issue 4 (6th November 2016) - Abrantes, Adelino António Artur; Rafacho, Alex; Rivero, Elena Riet Correa; Mariano, Fernanda Viviane; Siqueira, Filipe Modolo; Gondak, Rogério Oliveira
Abstract: The selection of an appropriate demineralizing solution in pathology laboratories depends on several factors such as the preservation of cellularity, urgency of diagnostic and financial costs. The aim of this study was to test different decalcification bone procedures in order to establish the best value of these in formalin‐fixed and paraffin‐embedded samples. Femurs were removed from 13 adult male Wistar rats to obtain 130 bone disks randomly divided into five groups that were demineralized in different concentrations of nitric acid (Group I); formic acid (Group II); acetic acid (Group III); EDTA, pH7.4 (Group IV) and Morsés solution (Group V). Serial, 3‐μm‐thick sections were obtained and stained with hematoxylin‐eosin to calculate the percentage of osteocyte‐occupied lacunae. The sections were also stained with Masson's trichrome in conjunction with picrosirius red under polarized light followed by a semi‐quantitative analysis to verify the adjacent muscle‐to‐bone integrity and preservation of collagen fibres. The highest percentage of osteocyte‐occupied lacunae was found with 10% acetic acid solution (95.64 ± 0.95%) and Group I (nitric acid) demanded the shorter time (0.8–5.7days). Of all solutions, 5% nitric acid incurred the lowest cost to achieve complete demineralization compared with other solutions ( p < .001). Group IV (EDTA) had the highest integrity of muscle and collagen type I and III ( P < 0.01). Demineralization with 10% acetic acid was the most effective at preserving bone tissue, while 5% EDTA was the best at maintaining collagen and adjacent muscle to bone. In conclusion, nitric acid at 5% showed the most efficient result as it balanced both time and cost as a demineralizing solution. Abstract : The selection of an appropriate demineralizing solution is proposed; Nitric acid at 5% had better results in the balance between time, cost and tissue preservation than other chelating or acid solutions for using in pathology laboratories.